2013
DOI: 10.1152/ajplung.00081.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor-1 in pulmonary arterial smooth muscle cells by endothelin-1

Abstract: Pisarcik S, Maylor J, Lu W, Yun X, Undem C, Sylvester JT, Semenza GL, Shimoda LA. Activation of hypoxia-inducible factor-1 in pulmonary arterial smooth muscle cells by endothelin-1. Am J Physiol Lung Cell Mol Physiol 304: L549 -L561, 2013. First published February 15, 2013 doi:10.1152/ajplung.00081.2012.-Numerous cellular responses to hypoxia are mediated by the transcription factor hypoxia-inducible factor-1 (HIF-1). HIF-1 plays a central role in the pathogenesis of hypoxic pulmonary hypertension. Under cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 71 publications
1
54
1
Order By: Relevance
“…In contrast, ET-1 failed to augment HIF-1α in aortic smooth muscle cells, suggesting a feature unique to PASMCs. 97 Since the primary source of ET-1 in vivo appears to be endothelial cells, these data, taken as a whole, suggest a possible model whereby enhanced HIF-2α expression in endothelial cells during CH produces ET-1, which then augments HIF-1α in PASMCs, initiating a feed-forward mechanism for upregulation of HIF-1 and, consequently, HIF target genes to promote the development of HPH.…”
Section: Mechanisms Of Hph: Lessons From Animal Modelsmentioning
confidence: 87%
“…In contrast, ET-1 failed to augment HIF-1α in aortic smooth muscle cells, suggesting a feature unique to PASMCs. 97 Since the primary source of ET-1 in vivo appears to be endothelial cells, these data, taken as a whole, suggest a possible model whereby enhanced HIF-2α expression in endothelial cells during CH produces ET-1, which then augments HIF-1α in PASMCs, initiating a feed-forward mechanism for upregulation of HIF-1 and, consequently, HIF target genes to promote the development of HPH.…”
Section: Mechanisms Of Hph: Lessons From Animal Modelsmentioning
confidence: 87%
“…In addition to regulating both Ca 2+ and pH homeostasis (566,666), HIFs also regulate other factors involved in the pathogenesis of PH, including ET-1 and VEGF [reviewed in (505)]. While hypoxia is an obvious stimulant for HIF activation, HIFs also can be upregulated under nonhypoxic conditions by a number of factors (505), including ET-1 (497). Moreover, HIF-1α protein is detectable in PASMCs from FHRs (72) and lungs of PAH patients (18,165), which is thought to be linked to mitochondrial dysfunction.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…This establishes that transient vasoconstriction and the accompanying ischemic time frame is capable of inducing a potent inflammatory reaction. Furthermore, we observed induction of genes for oxidative stress linked proteins, such as Hif1a, Myc and Sod2/MnSOD at 24 h. Recent studies have demonstrated ET-1-dependent induction of Hif1a mRNA (Li et al, 2012;Pisarcik et al, 2013), with no documented effects on Sod2 and Myc. Intriguingly, statistically significant inductions of Ifnb, Tnf and Myc were also observed on the contralateral side of the brain, sampled at the same site, suggesting that a high degree of crosstalk exists between the injured hemisphere and its contralateral counterpart.…”
Section: Discussionmentioning
confidence: 47%